Safety and immunogenicity of a parenteral P2-VP8-P[8] subunit rotavirus vaccine in toddlers and infants in South Africa: a randomised, double-blind, placebo-controlled trial. Issue 8 (August 2017) - Groome, Michelle J; Koen, Anthonet; Fix, Alan; Page, Nicola; Jose, Lisa; Madhi, Shabir A; McNeal, Monica; Dally, Len; Cho, Iksung; Power, Maureen; Flores, Jorge; Cryz, Stanley
Summary: Background: Efficacy of live oral rotavirus vaccines is reduced in low-income compared with high-income settings. Parenteral non-replicating rotavirus vaccines might offer benefits over oral vaccines. We assessed the safety and immunogenicity of the P2-VP8-P[8] subunit rotavirus vaccine at different doses in South African toddlers and infants. Methods: This double-blind, randomised, placebo-controlled, dose-escalation trial was done at a single research unit based at a hospital in South Africa in healthy HIV-uninfected toddlers (aged 2 to <3 years) and term infants (aged 6 to <8 weeks, without previous rotavirus vaccination). Block randomisation (computer-generated, electronic allocation) was used to assign eligible toddlers (in a 6:1 ratio) and infants (in a 3:1 ratio) in each dose cohort (10 μg, followed by 30 μg, then 60 μg if doses tolerated) to parenteral P2-VP8-P[8] subunit rotavirus or placebo injection. The two highest tolerated doses were then assessed in an expanded cohort (in a 1:1:1 ratio). Parents of participants and clinical, data, and laboratory staff were masked to treatment assignment. P2-VP8-P[8] vaccine versus placebo was assessed first in toddlers (single injection) and then in infants (three injections 4 weeks apart). The primary safety endpoints were local and systemic reactions within 7 days after each injection, adverse events within 28 days after each injection, and all serious adverse events, assessed in toddlers and infants who received at least one dose. In infants receiving all study injections, primary immunogenicity endpoints were anti-P2-VP8-P[8] IgA and IgG and neutralising antibody seroresponses and geometric mean titres 4 weeks after the third injection. This trial is registered atClinicalTrials.gov, numberNCT02109484 . Findings: Between March 17, 2014, and Sept 29, 2014, 42 toddlers (36 to vaccine and six to placebo) and 48 infants (36 to vaccine and 12 to placebo) were enrolled in the dose-escalation phase, in which the 30 μg and 60 μg doses where found to be the highest tolerated doses. A further 114 infants were enrolled in the expanded cohort between Nov 3, 2014, and March 20, 2015, and all 162 infants (12 assigned to 10 μg, 50 to 30 μg, 50 to 60 μg, and 50 to placebo) were included in the safety analysis. Serum IgA seroresponses were observed in 38 (81%, 95% CI 67–91) of 47 infants in the 30 μg group and 32 (68%, 53–81) of 47 in the 60 μg group, compared with nine (20%, 10–35) of 45 in the placebo group; adjusted IgG seroresponses were seen in 46 (98%, 89–100) of 47 infants in the 30 μg group and 47 (100%; 92–100) of 47 in the 60 μg group, compared with four (9%, 2·5–21) of 45 in the placebo group; and adjusted neutralising antibody seroresponses against the homologous Wa-strain were seen in 40 (85%, 72–94) of 47 infants in both the 30 μg and 60 μg groups, compared with three (7%, 1·4–18) of 45 participants in the placebo group. Solicited reactions following any injection occurred with similar frequency and severity in participants receiving vaccine and those receiving placebo. Unsolicited adverse events were mostly mild and occurred at a similar frequency between groups. Eight serious adverse events (one with placebo, two with 30 μg, and five with 60 μg) occurred in seven infants within 28 days of any study injection, none of which were deemed related to study treatment. Interpretation: The parenteral P2-VP8-P[8] vaccine was well tolerated and immunogenic in infants, providing a novel approach to vaccination against rotavirus disease. On the basis of these results, a phase 1/2 trial of a trivalent P2-VP8 (P[4], P[6], and P[8]) subunit vaccine is underway at three sites in South Africa. Funding: Bill & Melinda Gates Foundation.